A New Deal for Native art : Indian arts and federal policy, 1933-1943 - McLerran, Jennifer (University of Arizona Press, 2009)
"As the Great Depression touched every corner of America, the New Deal promoted indigenous arts and crafts as a means of bootstrapping Native American peoples. But New Deal administrators' romanticization of indigenous artists predisposed them to favor pre-industrial forms rather than art that responded to contemporary markets. Jennifer McLerran reveals how positioning the native artist as a pre-modern Other served the goals of New Deal programs--and how this sometimes worked at cross-purposes with promoting native self-sufficiency. She describes federal policies of the 1930s and early 1940s that sought to generate an upscale market for Native American arts and crafts. And by unraveling the complex ways in which commodification was negotiated and the roles that producers, consumers, and New Deal administrators played in that process, she sheds new light on native art's commodity status and the artist's position as colonial subject. This book will be of interest to historians and artist alike and Native peoples magazine calls it 'a fascinating read for students of American Indian art'."--Back cover